An Applying Buddha’s Conduct (Buddhakij) in Developing the Quality of Life of Siam’s Monks in Kedah, Malaysia - Candhasaro, PhrakruSamuChader; Panasree, Sitthichok; PhrakruKositwattananukul; PhrakruKosolattakit; Anothai, Sawat (Academic MCU Buriram Journal, 2023)
The purpose of this research were: 1) to study the concept of developing the quality of life of Siam’s monks in Kedah, Malaysia, 2) to study the Buddha’s Conduct (Buddhakij) appearing in the Buddhist scriptures, and 3) to apply the Buddha’s Conduct (Buddhakij) in developing the Quality of Life of Siam’s Monks in Kedah, Malaysia. It is qualitative research, focuses on document studies and in-depth interviews. The research results found that: 1. The concept of developing the quality of life of Siam’s monks in Kedah, Malaysia. Developing the quality of life is the development of the quality of life of people in different dimensions from their original condition to be better both physically and mentally. It is learning and understanding the truth of life that is constantly changing to be able for living happily in society. 2. The Buddha’s Conduct (Buddhakij) appearing in the Buddhist scriptures. The Buddha’s Conduct (Buddhakij) refers to the five routine principles that the Buddha practiced daily, namely: 1) in the morning, he goes out to offer alms to helps the world citizen; 2) in the evening, he teaches the Dhamma; 3) in the late evening, he gives sermons to monks; 4) midnight, he answered the question of the angels, and 5) in the early morning, he examined the creatures that should be visited. The Buddha performed these five activities as a daily routine that had not been spared for 45 years. 3. An Application of the Buddha’s Conduct (Buddhakij) in Developing the Quality of Life of Siam’s Monks in Kedah, Malaysia. The Buddha’s Conduct (Buddhakij) is the Buddha’s activities daily routines that the Buddha performs can be used as an applied guideline for developing the quality of life of Siam’s monks in Kedah, Malaysia in four aspects namely physical, moral, mental and intellectual for a good quality of life.